A survey of anxiety and burnout in the radiology workforce of a tertiary hospital during the COVID‐19 pandemic. Issue 2 (16th February 2021) - Huang, Hian Liang; Chen, Robert Chun; Teo, Irene; Chaudhry, Isha; Heng, Ai Ling; Zhuang, Kun Da; Tan, Hiang Khoon; Tan, Bien Soo
Abstract: Introduction: We aimed to study anxiety and burnout among Division of Radiological Sciences (RADSC) staff during the COVID‐19 pandemic and identify potential risk and protective factors. These outcomes were compared with non‐RADSC staff. Methods: A cross‐sectional online study was conducted between 12 March and 20 July 2020 in the largest public tertiary hospital receiving COVID‐19 cases. Burnout and anxiety were assessed with the Physician Work‐Life Scale and the Generalized Anxiety Disorder‐7 Scale, respectively. Workplace factors were examined as potential risk and protective factors using multivariable ordinary least squares regression analyses, adjusting for pertinent demographic characteristics. Results: RADSC staff ( n = 180) and non‐RADSC staff ( n = 1458) demonstrated moderate‐to‐severe anxiety rates of 6.7 and 13.2 % and burnout rates of 17.8 and 23.9 %, respectively. RADSC staff reported significantly lower anxiety (mean ± SD: 4.0 ± 3.7 vs 4.9 ± 4.5; P ‐value < 0.05), burnout (mean ± SD: 1.9 ± 0.7 vs 2.1 ± 0.8; P ‐value < 0.01), increased teamwork (82.2% vs 74.1%; P ‐value < 0.05) and fewer night shifts (36.7% vs 41.1%; P ‐value < 0.01). Among RADSC staff, higher job dedication was associated with lower anxiety (b (95% CI) = −0.28 (−0.45, −0.11)) and burnout ( b (95% CI) = −0.07 (−0.11, ‐0.04)), while longer than usual working hours was associated with increased anxiety ( b (95% CI) = 1.42 (0.36, 2.45)) and burnout ( b (95% CI) = 0.28 (0.09, 0.48)). Conclusions: A proportion of RADSC staff reported significant burnout and anxiety, although less compared to the larger hospital cohort. Measures to prevent longer than usual work hours and increase feelings of enthusiasm and pride in one's job may further reduce the prevalence of anxiety problems and burnout in radiology departments.